2020
DOI: 10.3390/genes11030272
|View full text |Cite
|
Sign up to set email alerts
|

Down Regulation and Loss of Auxin Response Factor 4 Function Using CRISPR/Cas9 Alters Plant Growth, Stomatal Function and Improves Tomato Tolerance to Salinity and Osmotic Stress

Abstract: Auxin controls multiple aspects of plant growth and development. However, its role in stress responses remains poorly understood. Auxin acts on the transcriptional regulation of target genes, mainly through Auxin Response Factors (ARF). This study focuses on the involvement of SlARF4 in tomato tolerance to salinity and osmotic stress. Using a reverse genetic approach, we found that the antisense down-regulation of SlARF4 promotes root development and density, increases soluble sugars content and maintains chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(70 citation statements)
references
References 80 publications
4
55
0
Order By: Relevance
“…However, stomatal conductance of the SlARF4-as phenotype did not change significantly under salt or Polyethylene glycol (PEG)-simulated water stress, compared with the control. Nonetheless, the WT showed a normal response to osmotic stress, with a significant decrease in stomatal conductance [ 47 ]. In our study, the epidermis of the upper leaves on arf4 plants showed smaller stomata than that of the WT leaves, and they did not immediately close upon initiation of the water deficit treatment; furthermore, the guard cells still retained their normal plumpness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, stomatal conductance of the SlARF4-as phenotype did not change significantly under salt or Polyethylene glycol (PEG)-simulated water stress, compared with the control. Nonetheless, the WT showed a normal response to osmotic stress, with a significant decrease in stomatal conductance [ 47 ]. In our study, the epidermis of the upper leaves on arf4 plants showed smaller stomata than that of the WT leaves, and they did not immediately close upon initiation of the water deficit treatment; furthermore, the guard cells still retained their normal plumpness.…”
Section: Discussionmentioning
confidence: 99%
“…The plant #5 bearing the desired mutation of SlARF4 was used for the water deficit study. More information about the SlARF4 CRISPR/Cas 9 lines generation could be found in the paper of Bouzroud et al [ 47 ]. Tomato SlARF4 knockout ( arf4 ) and pARF4::GUS plants were grown in a controlled climate room (25 ± 5 °C) under a 16 h/8 h (light/dark) photoperiod at the South China Agricultural University.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Arabidopsis ARF2 may affect seed size and drought tolerance through regulating ABA signaling [ 52 ]. In addition, transgenic expression of a sweet potato IbARF5 in Arabidopsis and downregulation of a tomato SlARF4 have been found to increase ABA content in the plants [ 53 , 54 ]. From ABA to auxin direction, an ABI3-like factor from the bean is known to bind an auxin-inducible promoter [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Auxin response factor (ARF) is one family of functionally distinct DNA-binding transcription factors found widely in all plant species ( Li SB et al, 2016 ). CRISPR/Cas9 knock-out of the arf4 transcription factor gene improved plant tolerance to salinity and osmotic stresses in tomato ( Bouzroud et al, 2020 ). Using the CRISPRa epigenome editor, Roca Paixão et al (2019) successfully fused dCas9 protein with a histone acetyltransferase (AtHAT1) and used this fused CRISPR/dCas9 system to target the abscisic acid (ABA)-responsive element-binding protein 1 (AREB1)/ABRE-binding factor 2 (ABF2).…”
Section: Crispr/cas Is a Robust And Powerful Tool For Precision Brementioning
confidence: 99%